2007
DOI: 10.1016/j.actamat.2007.06.030
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural evolution and formation of nanocrystalline intermetallic compound during surface mechanical attrition treatment of cobalt

Abstract: Nanocrystalline intermetallic Co 3 Fe 7 was produced on the surface of cobalt via surface mechanical attrition (SMA). Deformationinduced diffusion entailed the formation of a series of solid solutions. Phase transitions occurred depending on the atomic fraction of Fe in the surface solid solutions: from hexagonal close-packed (<4% Fe) to face-centered cubic (fcc) (4-11% Fe), and from fcc to body-centered cubic (>11% Fe). Nanoscale compositional probing suggested significantly higher Fe contents at grain bounda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
25
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(27 citation statements)
references
References 63 publications
2
25
0
Order By: Relevance
“…The diffusion of adatoms, molecules and atomic clusters at material surfaces not only affects the structure evolution during polycrystalline [1][2][3][4][5][6][7] and epitaxial thin film growth [6][7][8][9][10] but also enables surface sensitive applications such as catalysis [7,[11][12][13], sintering [14,15], gas sensing [16,17], as well as molecular self-assembly [18,19] and crystal growth [20][21][22]. From a vapor phase condensation point of view surface diffusion, or lack thereof, is and has been one of the most fundamental concepts employed in explaining structure evolution in general and the formation of the metastable phases in particular.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The diffusion of adatoms, molecules and atomic clusters at material surfaces not only affects the structure evolution during polycrystalline [1][2][3][4][5][6][7] and epitaxial thin film growth [6][7][8][9][10] but also enables surface sensitive applications such as catalysis [7,[11][12][13], sintering [14,15], gas sensing [16,17], as well as molecular self-assembly [18,19] and crystal growth [20][21][22]. From a vapor phase condensation point of view surface diffusion, or lack thereof, is and has been one of the most fundamental concepts employed in explaining structure evolution in general and the formation of the metastable phases in particular.…”
Section: Introductionmentioning
confidence: 99%
“…From a vapor phase condensation point of view surface diffusion, or lack thereof, is and has been one of the most fundamental concepts employed in explaining structure evolution in general and the formation of the metastable phases in particular. Surface diffusion governs the structure evolution of coating materials, often leading to metastable phase formation due to kinetic limited vapor phase condensation processes [2][3][4][5][6][7]. Much of materials science deals with the relationship between structure and properties.…”
Section: Introductionmentioning
confidence: 99%
“…The method of severe plastic deformation (SPD) is of great interest to the production of ultrafine-grain or nano-grain microstructures for metals and alloys [1][2][3][4][5][6][7][8][9][10][11][12][13]. Several SPD methods for producing bulk metals with sub-micrometer or nanometer grain size have been reported, e.g., high pressure torsion (HPT) [4,5], equal channel angular pressing (ECAP) [6,7] and accumulative roll bonding (ARB) [8].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] With the formation of high density nanoscaled growth-in twins, Lu et al 1) obtained a pure copper with a tensile strength above 1 GPa and Zhang et al…”
Section: Introductionmentioning
confidence: 99%
“…Up to now, high density nanoscaled twins could be formed via chemical or physical depositions, such as pulsed electrodeposition, 1) magnetron-sputter deposition, 2) surface mechanical attrition treatment 3) and dynamic plastic deformation. 4) Recently, Zhang et al and Zhou et al reported that nanoscaled phases could be obtained in a coarse-grained alloy by electric current pulse (ECP) treatment.…”
Section: Introductionmentioning
confidence: 99%